Specific Characteristics of Drying Storage of Fruits and Vegetables (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article provides information from the literature on methods of drying dried fruits and vegetables. On this basis, along with the development of export of dry products in our country, it is possible to achieve a number of positive achievements in the field of agriculture. In particular, dry goods are very convenient for loading, unloading and storage, dry goods are also an invaluable quality product for various expeditions and passengers.